SURVEI JENTIK NYAMUK Aedes aegypti DI PERUMAHAN WILAYAH KERJA PUSKESMAS MENTENG KOTA PALANGKA RAYA - Rinny Ardina; Nurhalina Nurhalina; Suratno Suratno; Dwi Purbayanti; Fera Sartika; Agus Agus (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
Severe dengue or Dengue Hemorrhagic Fever (DHF) occurrence in Palangka Raya frequently becomes epidemic. The morbidity rate (incidence rate) of DHF cases in Central Kalimantan in 2016 reached 69.1 per 100,000 population with the mortality rate (fatality rate) of 1.4%. The morbidity rate reached 278.4 per 100,000 population in Palangka Raya, the second place after North Barito regency. Based on the Ministry of Health Republic of Indonesia’s Strategic Planning (Renstra), targets for dengue fever in 2016 should be <49 per 100,000 population, Central Kalimantan Province has not achieved the target yet. The Central Kalimantan Provincial Health Office reported the epidemy of DHF in 2017 occurred in the working area of Menteng Community Health Center. The report found a case that all family members of a household suffered from DHF. This community service aimed to educate the community to survey of dengue larvae independently, to develop the community’s knowledge and awareness about the importance of support from larvae monitoring speculator Juru Pemantau Jentik (also briefly known as Jumantik) and to increase community participation in DHF prevention movement in Palangka Raya. The method of this community service used site survey, observation, interview, larva examination and reporting of results. The survey activity of larvae showed that Aedes aegypti mosquito larvae were identified in 13.3% of the houses, mostly found in bathtubs, water shelters and water container of water dispensers.